BIOSENSORS: IMPLEMENTATION AND OUTLOOK IN THE CONTROL AND PROCESS QUALITY AND FOODSTUFFS - JIMÉNEZ C, Claudio; LEÓN P., Daniel E. (Vitae, 2009)
The food, drink and related industries require analytical methods to secure physico-chemical, microbiological, bromatological sensory quality and stability of raw materials, processes and products. These methods must offer real time data that allow to control and to monitor each process to safeguard the innocuity of the nutritional products. The traditional analytical methods have to deal with gravimetric, volumetric and colorimetric determinations with limited sensitivity levels for trace determination, and with little specificity. Although the chromatographic methods show highly reproducible results and the limit of detection is as low as parts per trillion, these methods are expensive and imply very exhaustive treatments of the sample. Biosensors are integrated devices consisting of a biological recognition element and a transducer capable of detecting the biological reaction and converting it into a signal which can be processed, becoming an important tool to check the quality and processes. The present approach shows promising advantages compared to traditional method. This paper presents a ten year development of these devices and their application to food investigation and similars; contributing with applications for the automated and not automated process control, mycotoxins detection, identification of antinutritional factors, residuality of traditional and emergent organic polluting agents (pesticides, antibiotics, hormones, dioxins, furanones, among others), monitor and microbiological control, presence of genetically modified organisms among others. The objective of this study is to review paper and updated information on the use of biosensors as a technology in food analysis and its advantages within the food security systems.